1993
DOI: 10.1007/bf03009472
|View full text |Cite
|
Sign up to set email alerts
|

Orbicular muscle akinesia in regional ophthalmic anaesthesia with pH-adjusted bupivacaine: effects of hyaluronidase and epinephrine

Abstract: The success rate and duration of lid amnesia after adding hyaluronidase and/or epinephrine to p H-adjusted bupivacaine was examined in a double-blind fashion in patients undergoing cataract surgery under local anaesthesia. A two-injection-site technique was used. For globe akinesia all patients (n = 120) received an inferolateral intraconal injection (3 m 0 of p H-adjusted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
14
2
1
Order By: Relevance
“…One-third of the patients in both groups reported mild pain during the anaesthetic procedure, the mean pain score being 2.3 in the bupivacaine group and 2.2 in the ........................................................................................................................................................................................................................................ Table 1 Akinesia scoring system [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One-third of the patients in both groups reported mild pain during the anaesthetic procedure, the mean pain score being 2.3 in the bupivacaine group and 2.2 in the ........................................................................................................................................................................................................................................ Table 1 Akinesia scoring system [10].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, equal concentrations of the two local anaesthetics were not used in this study, as good akinesia is mandatory in cataract surgery. Bupivacaine has been shown to provide adequate globe akinesia and sensory analgesia as a 0.75% concentration and consequently has been recommended for regional ophthalmic anaesthesia [10,15]. Epidural studies comparing 0.75% bupivacaine with 1% ropivacaine have shown that bupivacaine provides an equally good sensory block as ropivacaine and a similar or a slightly better motor block [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of peribulbar compared with the retrobulbar technique appear to include a reduced incidence of serious complications such as brain stem anaesthesia, intravascular injection, scleral perforation and retrobulbar haemorrhage [1]. Various additives to the local anaesthetic have been used in an attempt to improve the quality of anaesthesia and operating conditions; mixtures of rapid onset and longer acting local anaesthetics, adrenaline, hyaluronidase and alkalinisation [2][3][4][5]. One disadvantage with peribulbar when compared with retrobulbar blockade is delayed or incomplete akinesia of the eye which may prolong the procedure and make the surgery more technically demanding [6].…”
mentioning
confidence: 99%
“…However it has a slow onset of action and frequent supplementations may be needed [2]. So many additives have been used have been used in peribulbar block to hasten the onset of akinesia and increase tissue diffusion such as hyaluronidase, [3] adrenaline, [4] clonidine, [5] corticosteroids, [6] sodium bicarbonate [7] and neuromuscular blocking agents [8]. These agents have many side-effects like allergic reaction, bradycardia, sedation, dryness of mouth, systemic neuromuscular blockade, etc.…”
Section: Introductionmentioning
confidence: 99%